Online Toll Payment System Using Image Processing: Efficient and Secure Digital Toll Payment System Using Image Processing (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In this 21st century, India is a developing country. To make India a developed country DIGITALIZATION can play vital role. India is currently going through the process of digitalization. Various fields are being digitalized by our Government. But at many places still traditional methods are being used. One such place is the Toll Plaza encountered on various highways. Traditional methods are very time consuming and also not secure. There is no platform till date to pay the toll fees digitally. And this causes very high rush on toll booths. This project will provide an Android App, which will help to pay toll fees through Mobile by using CreditDebit card .This approach will go eco-friendly because of paperless transaction. Project uses the GPS technology to track the location of the vehicle. When the location of mobile enters in range of 2 km from toll booth, a notification will be sent on user mobile with details of toll and charges. The user pays toll charges without having to stop at the upcoming toll booth.